EXAMINING DEVELOPMENT PROGRAMS AND THEIR IMPACT ON WOMEN-LED STARTUPS IN CHHATTISGARH (International Journal of Food and Nutritional Sciences, 2022)
With the rise of economic liberalization and globalization, there has been a notable increase in women entrepreneurs on a global scale. Women are increasingly recognized as significant contributors in the entrepreneurial landscape, undertaking the challenging role of achieving personal fulfillment and economic independence. Their participation not only stimulates capital formation and wealth creation within their countries but also imbues entrepreneurship with elements of risk, change, challenge, and growth. Despite these strides, women entrepreneurs encounter numerous challenges such as financial constraints, marketing hurdles, manufacturing issues, and labor-related difficulties. Additionally, a significant number of women entrepreneurs start their businesses without formal training, which often contributes to business failures. Recognizing the importance of overcoming these obstacles, the Government of India has implemented various development initiatives and policy measures to nurture a culture of innovation and entrepreneurship. These efforts aim to empower women entrepreneurs and integrate them more fully into the national development agenda. It is imperative to identify and support aspiring entrepreneurs regardless of factors such as caste, creed, or gender, providing them with essential training and ongoing support mechanisms. The involvement of women in entrepreneurship is vital for comprehensive and balanced national development. Their active participation ensures that the process of development is inclusive and robust, benefiting society as a whole.